Healthcare provider counselling for weight management behaviours among adults with overweight or obesity: a cross-sectional analysis of National Health and Nutrition Examination Survey, 2011–2018. Issue 11 (23rd November 2020) - Greaney, Mary L.; Cohen, Steven A.; Xu, Furong; Ward-Ritacco, Christie L; Riebe, Deborah
Abstract : Objectives: To determine if adults with overweight or obesity received counselling from their healthcare providers (HCPs) to lose weight and/or adopt healthful behaviours associated with weight loss, and whether they took action on their HCPs' recommendations. Design: Cross-sectional analysis of 2011–2018 National Health and Nutrition Examination Survey (NHANES) data. Sample: NHANES respondents aged 18+ who were overweight/obese and had seen an HCP in the previous 12 months (n=13 158). Methods: Respondents reported if their HCPs recommended they control/lose weight, increase exercise/physical activity (PA) and/or reduce fat/calorie intake, and if they adopted the offered recommendation(s). Weighted logistic regression models examined receipt of HCP counselling by sex, age, race/ethnicity, and weight status accounting for demographic characteristics and complex sampling. Similar analyses examined reported adoption of HCPs' recommendations. Results: The sample was 53.1% women, 45.0% were overweight and 55.0% had obesity. In total, 40.4% received counselling to control/lose weight, 49.5% to increase exercise/PA and 38.9% to reduce fat/calorie intake. The following groups were less likely (p<0.001) to receive counselling: men; younger adults (aged 18–39) versus middle-aged (aged 40–64) and older adults (aged 65+); White versus Black and Hispanic respondents; overweight respondents versus respondents with obesity. Approximately half of those advised to make changes reported doing so (53.6% controlled/lost weight, 57.3% increased exercise/PA, 51.8% reduced fat/calorie intake). Differences in the adoption of recommendations were identified by sex, age group, race/ethnicity and weight status (all p<0.05); women, middle-aged and older adults, Black and Hispanic respondents and individuals with obesity were more likely to adopt one or more recommendations. Conclusion: Most respondents did not receive HCP counselling, and approximately half of those who received counselling reported taking action. HCPs may need training to provide counselling and to offer recommendations tailored to the social contexts of populations less likely to adopt weight control related recommendations.